The Potential Role of Nicotine in the Treatment of Learning and Memory Impairment after REM Sleep Deprivation - Long, Idris; Abd Rashid, Norlinda (2015)
Sleep deprivation has become a contributing factor to the world’s health concerns such as cardiovascular disease, mental illness and inattentiveness in occupationand decision making. It can also disturb synaptic plasticity that can lead to learning and memory impairment. Therefore, boosting cholinergic activity using acetylcholine imitator that can be found in the tobacco plant, known as nicotine, is essential in reversing the negative influences of sleep loss in the brain. Thus, studies on the effects of nicotine treatment on molecular mechanisms and structural changes of hippocampal brain cells are vital in order to gain more understanding and to overcome the detrimental consequencesof learning and memory impairment related to sleep divest.